LEARNING INNOVATIONS IN STEAM-BASED EARLY CHILDHOOD EDUCATION DEVELOP 21st CENTURY SKILLS - Elis Hamida; Hendri Hendri; Merri Sri Hartati; Afriza Fitriani (International Journal of Teaching and Learning, 2025)
Early childhood education (PAUD) is an important foundation in developing 21st century skills. STEAM-based learning innovations (Science, Technology, Engineering, Art, and Mathematics) can be one of the solutions to develop 21st century skills in early childhood education children. This study aims to find out how learning innovations in STEAM-based early childhood education can develop 21st century skills in early childhood children. The results show that the STEAM approach can help children develop critical thinking, creativity, and problem-solving skills. The implementation of the STEAM approach in PAUD can also improve children's ability to work together and communicate. However, the implementation of the STEAM approach in early childhood education also has several challenges, such as a lack of adequate resources and facilities to support STEAM learning. Therefore, efforts need to be made to improve the implementation of the STEAM approach in early childhood education in order to help children develop the 21st century skills needed to succeed in the future. Thus, this research can contribute to the development of more effective and innovative early childhood education.